KETERAMPILAN BERPIKIR KRITIS MENGGUNAKAN MODEL CONTEXTUAL TEACHING AND LEARANING DI SEKOLAH DASAR - Masniladevi Masniladevi (Universitas Negeri Padang, 2017)
Learning activities in primary schools are still dominated by teachers, consequently the students' critical thinking skills are low. The purpose of this study is to describe the implementation and improvement of students' critical thinking skills on the characteristics of wake up flat by using Contextual teaching and learning model. The results showed an improvement in the observation of students' critical thinking skills as well as aspects of teachers and students. The students' critical thinking ability in cycle I was 69 and increased in cycle II to 86. The result of observation of student aspect in cycle I was 76.75% with good qualification, and increased in cycle II to 92% with excellent qualification. It was concluded that, Contextual Teaching And Learning model can improve students' mathematical critical thinking ability.Keywords: critical thinking skills; Contextual Teaching And Learning model